Posterior reversible encephalopathy syndrome (PRES) of the isolated brainstem. Issue 4 (7th April 2022) - Hayashi, Yosuke; Hashida, Tomoaki; Yazaki, Megumi; Uchida, Tomohiko; Watanabe, Eizo
Abstract: A 71‐year‐old man had disordered consciousness whose Glasgow Coma Scale was E4V1M5. His blood pressure was high, but there was no abnormality in the cerebrospinal fluid examination. The MRI finding reveals a high‐intensity area at the pons without the blood flow interruption. Thus, he has diagnosed with brainstem PRES. Abstract : The typical MRI finding of PRES is the presence of a symmetric vasogenic edema in the parietal and occipital lobes. However, up to the 27% of cases occur at the brainstem, and it is imperative to remember this less frequent localization.